Fracture and damage of concrete and rock : FDCR-2 : proceedings of the Second International Conference on Fracture and Damage of Concrete and Rock, Vienna, Austria, 9-13 November 1992 /: FDCR-2 : proceedings of the Second International Conference on Fracture and Damage of Concrete and Rock, Vienna, Austria, 9-13 November 1992. ([2014?]) - Unknown
No abstract available